Dragonfruit - Lucier, Makiia (New York, NY Clarion Books, 2024)
"In the old tales, it is written that the egg of a seadragon, dragonfruit, holds within it the power to undo a person's greatest sorrow. But as with all things that offer hope when hope has gone, the tale comes with a warning. Every wish demands a price. Hanalei of Tamarind is the cherished daughter of an old island family. But when her father steals a seadragon egg meant for an ailing princess, she is forced into a life of exile. In the years that follow, Hanalei finds solace in studying the majestic seadragons that roam the Nominomi Sea. Until, one day, an encounter with a female dragon offers her what she desires most: a chance to return home, and to right a terrible wrong. Samahtitamahenele, Sam, is the last remaining prince of Tamarind. But he can never inherit the throne, for Tamarind is a matriarchal society. With his mother ill and his grandmother nearing the end of her reign, Sam is left with two choices: to marry, or to find a cure for the sickness that has plagued his mother for ten long years. When a childhood companion returns from exile, she brings with her something he has not felt in a very long time--hope. But Hanalei and Sam are not the only ones searching for the dragonfruit. And as they battle enemies both near and far, there is another danger they cannot escape . . . that of the dragonfruit itself"--
113615
Keywords: Magic; Dragons; Man-woman relationships; Kings and rulers; Adventure and adventurers; Fantasy; Young adult fiction